Anxiety and depression associated with vertigo: a cross sectional study from India - Asha, C. S.; Kumar, C. T. Sudhir; Punnoose, Varghese P.; Jacob, Joe (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Vertigo is a common clinical symptom in the community as well as in specialist settings. Depression and anxiety are common among vertigo patients and have a significant impact on the course of illness. Methods: This study was conducted at the outpatient clinics of Department of ENT, Government Medical College, Kottayam. Zung self-rating anxiety and Zung self-rating depression scales were used. Results: There were 158 patients in the study. The commonest diagnosis was benign paroxysmal positional vertigo (BPPV) (76; 48.1%) followed by migrainous vertigo (MV) (41; 25.9%), Meniere’s disease (MD) (31; 19.6%) and vestibular neuronitis (VN) (10; 6.3%). 74 (46.83%) patients had depression. Depression was most prevalent among MD (26; 83.87%) followed by MV (29; 70.73%). Mean depression score was highest with MD (58; SD=8.136) followed by MV (54.29; SD=10.441). 70 (44.03%) patients had anxiety. 50 being women and 20 men. A diagnosis of anxiety was most common in MD (25; 80.6%) followed by MV (33; 80.5%). Mean anxiety score was highest in MD (56.48; SD=11.003) followed by MV (54.15; SD=12.041), A diagnosis of anxiety was most common among patients with MD (25; 80.6%) followed by MV (33; 80.5%). Conclusions: There is a high prevalence of depression and anxiety in Meniere’s disease and migrainous vertigo in India as evidenced by this study. Identification and appropriate management of coexisting mental health problems to address the disability, poor quality of life and protracted course is an integral part of managing vertigo.